Biomarkers for Inflammatory Breast Cancer: Diagnostic and Therapeutic Utility - Dobiasova B (Dove Medical Press, 2020)
Barbora Dobiasova, Michal Mego 2nd Department of Oncology, Comenius University, Faculty of Medicine, National Cancer Institute, Bratislava, Slovak RepublicCorrespondence: Michal Mego 2 nd Department of Oncology, Comenius University, Faculty of Medicine, National Cancer Institute, Klenova 1, Bratislava 833 10, Slovak RepublicTel +421-2-59378366Fax +421-2-54774943Email misomego@gmail.comAbstract: Inflammatory breast cancer (IBC) is a rare and highly aggressive subtype of advanced breast cancer. The aggressive behavior, resistance to chemotherapy, angiogenesis, and high metastatic potential are key intrinsic characteristics of IBC caused by many specific factors. Pathogenesis and behavior of IBC are closely related to tumor surrounding inflammatory and immune cells, blood vessels, and extracellular matrix, which are all components of the tumor microenvironment (TME). The tumor microenvironment has a crucial role in the local immune r09esponse. The communication between intrinsic and extrinsic components of IBC and the abundance of cytokines and chemokines in the TME strongly contribute to the aggressiveness and high angiogenic potential of this tumor. Critical modes of interaction are cytokine-mediated communication and direct intercellular contact between cancer cells and tumor microenvironment with a variety of pathway crosstalk. This review aimed to summarize current knowledge of predictive and prognostic biomarkers in IBC.Keywords: inflammatory breast neoplasms, biomarkers, tumor microenvironment, targeted therapy